Effect of using one versus two growth promoting implants on the gains of nursing calves - Corah, L.R.; McKee, M.; Schalles, R.R. (Kansas State University. Agricultural Experiment Station, 2011)
One hundred twenty-seven suckling calves were allotted to one of three treatments: (1) Control group - not implanted (2) Implanted (Ralgro) once during sucking period (3) Implanted (Ralgro) twice during sucking period - at average age of 44 days and 70 days later Using one Ralgro implant improved the weight at weaning by 8.4 pounds, while re-implanting, thus utilizing two implants during the suckling phase, resulted in an extra 43.0 pounds.
What's Ahead for Cattlemen? is known as Cattlemen’s Day, 1977
Keywords: Beef; Growth; Implants; Gain